William R. Plewman, The Toronto Daily Star, and the Reporting of the Winnipeg General Strike - Dupuis, Michael (Labour / Le Travail, 2006)
The article introduces eight documents on reporting of the Winnipeg General Strike of 1919 by the Toronto Daily Star's William Plewman. Also included are transcripts of 1972 interviews with Plewman's brother, Charles, who was also in Winnipeg at the time, as well as with William Plewman's son, Richard. Broadly sympathetic to labour issues, the Star's coverage of the strike was considered the most comprehensive and impartial.
Keywords: GENERAL strikes; JOURNALISM – Editing; LABOR market; LEGISLATIVE bodies; Labor disputes; Ontario; PLEWMAN; Charles; STRIKES & lockouts; Toronto (Ont.)